The strength of as cast iron and normalized cast iron subjected to cyclic loading - Leonavičius, Mindaugas (Strojniški vestnik, 2006)
This paper presents the results of an experimental and analytical investigation of the high-cycle fatigue of special as-cast and normalized irons, which later in the text are referred to as GI (grade iron) and SGI (spherical graphite iron). Well-known types of cast iron have been modified toachieve better mechanical properties and an improved resistance to crack formation and development as well as propagation. The defined values of the mechanical properties show that the normalizing changes the microstructure, enlarges the plasticity and makes uniform the limits of yield and strength. The microstructures of the investigated as-cast irons include graphite of different sizes, which, after the heat treatment, acquire a spherical shape, unify and reduce in size, and the whole microstructure becomes finer. After testing the compact eccentric tension CT (ASTM) specimens, the crack-growth rate versus the stress intensity factor range for the fatigue diagrams were constructed, and the threshold stress intensity ranges were determine for GIas cast iron dKth = 6.5 to 8.6 MPa; for GI normalized cast iron dKth = 8.2 to 10.3 MPa; for SGI as cast iron dKth = 8.0 to 9.6 MPa, and for SGI normalized cast iron dKth = 8.7 to 9.8 MPa. The significant differences in the threshold stress intensity factors were determined and related to the structural imperfections at the different sites of specimens formed during themanufacturing and normalization process. For specimens of as-cast and normalized cast iron, the dependence of DKth on the crack size was observed. An additional investigation and the fracture analysis show that it was influenced by the absence of structural uniformity. The suggested analytical expression of the DKth and the dependence of the mechanical properties can be applied for calculating the strength of cyclically loaded large-sized parts.
Keywords: lito železo; utrujanje materialov; lom materialov; razpoke; normalizacija; trdnost; mehanske lastnosti